Apunts per a una lectura de la poètica de la resistència en Carmelina Sánchez-Cutillas i Vicent Andrés Estellés. - MIRA NAVARRO, IRENE (Scripta, 2021)
This paper aims to explore the poetry of the 60s of Carmelina Sánchez-Cutillas in contrast with the poetry of Vicent Andrés Estellés as an example of «poetics of the resistance» proposed by the authors Cornelia Gräbner and David Wood (2010). On the one hand, we will analyze the work of the two poets like authors that form part of the cultural resistance during the years of the dictatorship because they are part of minoritised literature. On the other hand, we will study how this situation permeates the content of the texts and articulates a «poetics of resistance». The poetic voices of these authors show through the verses his ideological dissent with the dictatorial frame, especially regarding the reflection of social conscience, gender conscience and national conscience.